PENGGUNAAN TERAK NIKEL SEBAGAI AGREGAT DALAM CAMPURAN BETON - Mustika, Wayan; Salain, I M. Alit K.; Sudarsana, I K. (JURNAL SPEKTRAN; Vol 4 No 2 (2016): Vol. 4, No. 2, Juli 2016DO - 10.24843/SPEKTRAN.2016.v04.i02.p05, 2016)
Nickel slag is one kind of nickel ore smelting waste after the combustion process. Production of nickel slag PT. Antam Pomalaa Kolaka Southeast Sulawesi province during the period 2011-2012 period approximately 1 million tons of slag / year, with a nickel content in ore processing of nickel is between 1.80% to 2.00%. Visually, the physical form of this nickel slag aggregate resembles. Research on the use of nickel slag as an aggregate in concrete mixture is carried out using a cylindrical specimen with a diameter of 15 cm and 30 cm high by 48 pieces were tested at 28 days with some variations in the mix. Variation 01, 100% natural aggregate, variation 02, nickel slag as coarse aggregate, variation 03, nickel slag as fine aggregate, and variation 04, nickel slag as coarse aggregate and fine aggregate. Aggregate gradation in the mixture is set and is designed so that it meets the specifications gradation mix for maximum aggregate size of 40 mm. The composition of the concrete mixture used is a mixture of concrete with the ratio of cement : fine aggegate : coarse aggregate is 1: 2: 3 in a weight ratio with cement water ratio (fas) is set at 0.5. The results showed that when compared with the use of natural agregate, terak nickel is used only as a coarse agregate, a fine agregate only and combined agregate coarse and fine agregates resulting slump values ??fell 39.47%, an increase of 55.26%, and an increase of 34.21%. As a coarse agregate, terak nickel increases the compressive strength, modulus of elasticity and splitting tensile strenght, respectively for 42.27%, 19.37% and 23.46%. As fine agregate, nickel terak resulting value of compressive strength, modulus of elasticity and tensile strength divided down respectively by 16.75%, 6.70% and 24.58%. As a combination of coarse and fine agregate, terak nickel increases the compressive strength, modulus of elasticity and splitting tensile strenght, respectively for 10.31%, 9.26% and 6.70%.
Keywords: nickel terak, value of slump, compressive strength, modulus of elasticity, splitting tensile strength